Secular Trend of Birth Height and Weight in a Population of Iranian Neonates during 1991 and 2011 - Chegeni 1, Maryam; Fotouhi 1, Akbar; Emamian 2*, Mohammad Hassan; Mohammad 1, Kazem (Shahroud Journal of Medical Sciences, 2016)
Background: The secular trend in growth is a well-documented and recurrent phenomenon in many developed and developing countries. In this study, we examined the secular trends in birth length and weight among Iranian neonates.Methods: This cross-sectional population-based survey was conducted between 1991 and 2011. Using a two-stage stratified cluster sampling, the birth weights and heights of neonates born in Shahroud, Iran were studied using health records from different households. The mean birth weights and heights for neonates were calculated every year. Secular trends were analyzed using linear regression models and joinpoint regression.Results: A random sample of 11,165 neonates was evaluated, and the mean birth weight of neonates during the investigation period was calculated. The mean birth weight changed from 3232.1±444.1 g in 1991 to 3204.1±436.9 g in 2011, and the mean birth height changed from 49.5±2.2 cm to 49.3±1.9 cm. The mean birth weights and heights between 1991 and 2011 were not significantly different; however, the birth weight increased by 6.75 g annually between 2000 and 2011 (P < 0.021), and the mean birth height increased by 0.03 cm annually between 2003–2011 and 1991–2003 (P = 0.009).Conclusions: The mean birth height and weight of neonates in Shahroud did not change significantly from 1991 to 2011; however, we found a significant improvement after 2000.